Does habitat complexity influence fish recruitment? - CHEMINÉE, A.; MERIGOT, B.; VANDERKLIFT, M. A.; FRANCOUR, P. (Mediterranean Marine Science, 2015)
Human activities facilitate coastal habitat transformation and homogenization. The spread of marine invasive species is one example. This in turn may influence fish recruitment and the subsequent replenishment of adult assemblages. We tested habitat complexity effect on fish (Teleostei) recruitment by experimentally manipulating meadows of the habitat-forming invasive macroalga Caulerpa taxifolia (Chlorophyta). Among the fourteen fish species recorded during the experiment, only two labrids (Coris julis and Symphodus ocellatus) settled in abundance among these meadows. Patterns in the abundance of these juveniles suggested that reduced tri-dimensional meadow complexity may reduce habitat quality and result in altered habitat choices and / or differential mortality of juveniles, therefore reducing fish recruitment and likely the abundance of adults.